The effect of logistics service quality on customer satisfaction and loyalty among Indonesian Gen Z TikTok shop customers with delivery discrepancy and return experience - Syafa'atul Utma; Juliani Trisnawati (Southeast Asian Journal of Service Management, 2026)
Logistics service quality is one of the important elements in e-commerce because logistics service quality not only affects customers' perceptions of the service but also determines the success in maintaining customer loyalty in the long term. This study is a replication of a previous study, which stated that the four dimensions of logistics service quality, namely order accuracy, order condition, timeliness, and handling of order discrepancies, have a positive and significant effect on customer satisfaction. In addition, customer satisfaction has also been proven to have a positive and significant impact on customer loyalty. The main focus of this study is to review the relationship between variables that have been studied previously in the context of online shopping platform users in Indonesia. The approach used in this study is quantitative, with analysis techniques using Partial Least Squares (PLS) and Structural Equation Modeling (SEM) with the help of IBM SPSS Statistics 24 and SmartPLS 3 software. Data were collected through an online questionnaire from 204 Indonesian Gen Z TikTok Shop customers who had experienced delivery discrepancies and completed product returns. The findings of this study indicate that the four dimensions of logistics service quality, which include order accuracy, order condition, timeliness, and handling of order discrepancies, significantly and positively affect customer satisfaction. Likewise, customer satisfaction has also been proven to have a positive and significant effect on customer loyalty.